2003
DOI: 10.1046/j.1460-9568.2003.02784.x
|View full text |Cite
|
Sign up to set email alerts
|

Connexin30‐deficient mice show increased emotionality and decreased rearing activity in the open‐field along with neurochemical changes

Abstract: Gap-junction channels in the brain, formed by connexin (Cx) proteins with a distinct regional/cell-type distribution, allow intercellular electrical and metabolic communication. In astrocytes, mainly the connexins 43, 26 and 30 are expressed. In addition, connexin30 is expressed in ependymal and leptomeningeal cells, as well as in skin and cochlea. The functional implications of the astrocytic gap-junctional network are not well understood and evidence regarding their behavioural relevance is lacking. Thus, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 42 publications
(88 reference statements)
2
70
0
Order By: Relevance
“…Indeed, it has been shown that Cx30 KO mice exhibit altered reactivity to novel environmental stimuli implying a role of Cx30 on neuronal activity (Dere et al, 2003). In this study, we found an interesting relationship between the monomeric and dimeric forms of Cx30 in activated astrocytes by Western blot analysis.…”
Section: Discussionsupporting
confidence: 58%
“…Indeed, it has been shown that Cx30 KO mice exhibit altered reactivity to novel environmental stimuli implying a role of Cx30 on neuronal activity (Dere et al, 2003). In this study, we found an interesting relationship between the monomeric and dimeric forms of Cx30 in activated astrocytes by Western blot analysis.…”
Section: Discussionsupporting
confidence: 58%
“…38 Gait abnormalities due to cerebellar dysfunction 39 or neurodegeneration have been reported in mouse models for lysosomal storage diseases, 40,41 genes within the Down syndrome critical region, 42 genes encoding presynaptic proteins, 43 deficiency of transcription factors, 20,21 musculoskeletal disorders, 44 and polyglutamine diseases. 45 Although the number of polymorphic polyglutamine repeats in human RAI1 is implicated in modulating the onset of spinocerebellar ataxia, 46 mice carry only four glutamines in this region, and polymorphic CAG repeats have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted loss of astrocyte Cx43 expression inhibits glucose delivery to OPCs and OPC proliferation, which in turn can influence oligodendrogenesis and oligodendrocyte metabolic support (76). In addition, double knockouts for the astrocyte hemichannels Cx43 and Cx30 develop widespread white matter pathology with impairment of oligodendrocyte maturation and myelin vacuolation, whereas mice with astrocyte-targeted loss of Cx43 or Cx30-null mice do not show signs of abnormal myelination (85)(86)(87). Double knockouts affecting both oligodendrocyte and astrocyte hemichannels (Cx47/ Cx30) develop a progressive phenotype with early vacuolization of myelin with microgliosis, astrogliosis, motor impairment, and early death (88).…”
Section: Mct1mentioning
confidence: 99%